Mesenchymal stem cells suppress CD8+ T cell‐mediated activation by suppressing natural killer group 2, member D protein receptor expression and secretion of prostaglandin E2, indoleamine 2, 3‐dioxygenase and transforming growth factor‐β. (December 2014) - Li, Mingfen; Sun, Xuyong; Kuang, Xiaocong; Liao, Yan; Li, Haibin; Luo, Dianzhong
Summary Bone marrow mesenchymal stem cells (BMSCs) inhibit immune cell responsiveness, and especially of T lymphocytes. We showed that BMSCs markedly inhibited the proliferation and cytokine production by CD8+ T cells by a cell‐to‐cell contact phenomenon and secretion of soluble factors. BMSCs down‐regulate the expression of natural killer group 2, member D protein (NKG2D) receptors on CD8+ T cells when co‐cultured with them. Moreover, CD8+ T cells that express low levels of NKG2D had impaired proliferation after triggering by a mitogen. The major histocompatibility complex (MHC) class I chain‐related (MIC) A/B molecule, which is a typical ligand for NKG2D, was expressed on BMSCs, and caused dampening of cell proliferation. Monoclonal antibody blocking experiments targeted to MIC A/B impaired CD8+ T cell function, as evaluated by proliferation and cytokine production. In addition, the production of prostaglandin E2 (PGE2), indoleamine 2, 3‐dioxygenase (IDO) and transforming growth factor (TGF)‐β1 were increased when BMSCs were co‐cultured with CD8+ T cells. The addition of specific inhibitors against PGE2, IDO and TGF‐β partially restored the proliferation of CD8+ T cells. Our results suggest that BMSCs suppress CD8+ T cell‐mediated activation by suppressing NKG2D expression and secretion of PGE2, IDO and TGF‐β. Our observations further confirm the feasibility of BMSCs as a potential adoptive cellular therapy in immune‐mediated diseases such as graft‐versus‐host disease (GVHD).